Ultrasound-Targeted Microbubble Destruction Alleviates Immunosuppression Induced by CD71+ Erythroid Progenitor Cells and Promotes PDL-1 Blockade Immunotherapy in the Lewis Lung Cancer Model - Tan, Xi; Yi, Cuo; Zhang, Yi; Tang, Najiao; Xu, Yali; Liu, Zheng (Frontiers in Oncology, 2021)
The CD71+ erythroid progenitor cells (CECs) exhibit distinctive immunosuppressive properties and regulate antitumor immunity to enable tumor growth. We presented a novel and noninvasive approach to improving immunity by targeting the splenic CECs via sonoporation generated by ultrasound-targeted microbubble destruction (UTMD). The systematic immunity enhanced by the reduction of PDL-1-expressing CECs also benefits the PDL-1 blockade therapy. In the Luis Lung Cancer (LLC) model, the study group was treated by UTMD for 10 minutes at the splenic area with or without anti-mouse PDL-1 intraperitoneal injection. The frequency of splenic CEC, lymphocyte, and cytokine production was analyzed by flow cytometry. Serum interleukin-2 (IL-2) were tested by ELISA. Tumor volume was evaluated by two-dimensional ultrasound. The UTMD treatment consisted of ultrasound sonication and Sonazoid™ microbubble injection through the caudal vein. The mechanic index (MI) of ultrasound was set between 0.98 and 1.03. The results showed a significant reduction of splenic CECs and increased frequency of CD8+ T cells treated by UTMD treatment in the late-stage tumor. Tumor growth could be inhibited by UTMD combined with PDL-1 blockade therapy. The frequencies of interferon-γ (INF-γ) producing CD8+ and CD4+ T cells were significantly increased after being treated by the combination of UTMD and PDL-1 blockade, while the reactive oxygen species (ROS) production and the fraction of the TGF-β producing CD11b+ cells were significantly decreased. These preliminary findings suggest that UTMD enhances immune response and facilitates PDL-1 blockade therapy by targeting immunosuppressive CECs in the spleen. Our study provides new aspects and possibilities for treating cancer-related infection and tumor control in oncology.